ANALISIS WAKTU EFEKTIF PENEBANGAN JENIS AKASIA (Acacia mangium) DI AREAL IUPHHK-HT PT INHUTANI II PULAU LAUT KALIMANTAN SELATAN - Dewi Ratna Wulan; Daniel Itta; Arfa Agustina Rezekiah (Universitas Lambung Mangkurat, 2020)
Felling is an activity for harvesting trees that has met the proper criteria for felling in a forest area. The harvesting of wood was the first step of a logging activity beginning with an activity done to cut wood the stump is efficient and safe. The objective of this study is to establish the amount of time needed in logging and knowing of productivity and performance in the logging activity to flat tophography and italic tophography. The benefits of this study are to be able to provide the company with information and to take into consideration the policy of logging activities in industrial plant forests. The research method used is the mathematical analysis method by means of adding up all work time components carried out during group logging activities according to flat tophography and italic tophography by using productivity and work performance formulas. The result of this study shows that the average amount of time required for acacia felling (acacia mangium) in topography was 0,04 trees/hours or 2,17 minutes/trees. Topography 25% tilted by 0,06 trees/hours or 3,49 minutes/trees and effective working time that is a flat topography of 2,06 hours with a percentage of working time 90,71 % and worktime ineffective by 9,29 percent. Tilted topography measures 3,32 hours with a total worktime effective 91,31 % and worktime ineffective by 8,69 %. The highest productivity is that 3,57 m3/hours and flat tophography by 1,75 m3/hours. Highest performance of labor is 130,52 m3/hours in flat topography and obliging topography 119 m3/hours. Should be able to monitor chain saws regularly to maximize work time in logging. Keyword: Logging; time logging; productivity work; job performance